Acute and Chronic Effects of Whole-Body Vibration on Balance, Postural Stability, and Mobility in Women With Multiple Sclerosis. Issue 4 (27th December 2018) - Freitas, Eduardo D. S.; Frederiksen, Christine; Miller, Ryan M.; Heishman, Aaron; Anderson, Mark; Pardo, Gabriel; Fjeldstad, Cecilie; Bemben, Debra A.; Bemben, Michael G.
The acute and chronic effects of whole-body vibration (WBV) on balance, postural stability, and mobility were evaluated in 21 women with relapsing-remitting multiple sclerosis (MS) randomly assigned to control (n = 9) or experimental (n = 12) groups. To assess acute responses, outcome variables were assessed before and immediately after a session of WBV (five 30-second bouts of vibration; frequency 30 Hz; amplitude 3 mm; 1-minute rest intervals) during their first visit (week 1) using field (Timed-Up and Go; 500-m walk; Berg Balance Scale) and laboratory tests (NeuroCom Balance Master and EquiTest System—Sensory Organization Test, Adaptation Test, Limits of Stability, Modified Clinical Test for Sensory Integration of Balance, Unilateral Stance, Tandem Walk, Step/Quick Turn). Acute responses were also measured after their fifth visit for only the Adaptation and Sensory Organization tests. For the chronic responses, participants were exposed to the WBV protocol once a week, for a total of 5 weeks, and then at week 5, were reassessed with the Adaptation and the Sensory Organization tests. Neither acute nor chronic exposure to the WBV protocols used in this study resulted in significant improvements ( P > .05) in balance, postural stability, or mobility as assessed by either field or laboratory tests. However, based on promising results from other studies that have used WBV with other clinical populations, either alone or in conjunction with exercise, additional studies that increase the dose of vibration exposure, both acutely and chronically, should be conducted in patients with MS.